Gastroesophageal Reflux Disease: Medical or Surgical Treatment?. (7th December 2009) - Liakakos, Theodore; Karamanolis, George; Patapis, Paul; Misiakos, Evangelos P.
Abstract : Background . Gastroesophageal reflux disease is a common condition with increasing prevalence worldwide. The disease encompasses a broad spectrum of clinical symptoms and disorders from simple heartburn without esophagitis to erosive esophagitis with severe complications, such as esophageal strictures and intestinal metaplasia. Diagnosis is based mainly on ambulatory esophageal pH testing and endoscopy. There has been a long-standing debate about the best treatment approach for this troublesome disease. Methods and Results . Medical treatment with PPIs has an excellent efficacy in reversing the symptoms of GERD, but they should be taken for life, and long-term side effects do exist. However, patients who desire a permanent cure and have severe complications or cannot tolerate long-term treatment with PPIs are candidates for surgical treatment. Laparoscopic antireflux surgery achieves a significant symptom control, increased patient satisfaction, and complete withdrawal of antireflux medications, in the majority of patients. Conclusion . Surgical treatment should be reserved mainly for young patients seeking permanent results. However, the choice of the treatment schedule should be individualized for every patient. It is up to the patient, the physician and the surgeon to decide the best treatment option for individual cases.